Why Does Idiosyncratic Risk Increase with Market Risk? - Söhnke M. Bartram; Gregory Brown; René M. Stulz (Center for Economic Studies and ifo Institute (CESifo), 2017)
From 1963 through 2015, idiosyncratic risk (IR) is high when market risk (MR) is high. We show that the positive relation between IR and MR is highly stable through time and is robust across exchanges, firm size, liquidity, and market-to-book groupings. Though stock liquidity affects the strength of the relation, it is strong for the most liquid stocks. The relation has roots in fundamentals. Higher market risk predicts greater idiosyncratic earnings volatility as well as dispersion and errors in analysts' earnings forecasts. Firm characteristics related to the ability of firms to adjust to higher uncertainty help explain the strength of the relation. We find evidence that the relation is weaker for firms with more growth options, which is con-sistent with the view that such options provide a hedge against macroeconomic uncertainty.
Keywords: G10; G11; G12; 330; uncertainty; idiosyncratic risk; market risk; growth options; liquidity; limits to arbitrage